PROSES MANUFAKTUR MESIN PEMBUAT ES KUBUS PORTABEL DENGAN KAPASITAS 25 KG - Fayyiz Ar-Robbany (2021)
Ice cubes are a solid form of water that has been cooled to 0℃. Currently, many industries such as cafes and small restaurants use ice cubes as a complement to their dishes, making ice cubes yourself will be cheaper. An ice cube machine produced by the factory has a large construction with a long construction time and an expensive price. Based on these problems, it is necessary to conduct research or design on cube ice making machines. The design is aimed at developing a more economical manufacturing process on a cube ice machine so that it can be utilized by small industries. The prototype made has an effective capacity of up to 25kg of ice per day. This prototype was completed with a total processing time of 2.91 hours, and a cost of Rp. 2,162,814,69-.